2020
DOI: 10.3847/2041-8213/abaeff
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Standard Siren Measurement of the Hubble Constant from the LIGO/Virgo Gravitational Wave Compact Object Merger GW190814 and Dark Energy Survey Galaxies

Abstract: We present a measurement of the Hubble constant H 0 using the gravitational wave (GW) event GW190814, which resulted from the coalescence of a 23 M ⊙ black hole with a 2.6 M ⊙ compact object, as a standard siren. No compelling electromagnetic counterpart has been identified for this event; thus our analysis accounts for thousands of potential host galaxies within a statistical framework. The redshift information is obtained from the photometric redshift (ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 78 publications
5
78
0
1
Order By: Relevance
“…The number of GW events in this new catalogue (50) is ∼4 times the number of events from the first two observational runs combined [3], allowing for the increasingly sensitive exploration of their mass, spin and merger redshift distributions [4]. As the statistical uncertainties in these distributions continue to drop with the growing number of detections, the population of GW events provides a unique, and increasingly powerful, avenue to probe a wide range of topics, including fundamental physics [5], cosmology [6,7], and astrophysics [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The number of GW events in this new catalogue (50) is ∼4 times the number of events from the first two observational runs combined [3], allowing for the increasingly sensitive exploration of their mass, spin and merger redshift distributions [4]. As the statistical uncertainties in these distributions continue to drop with the growing number of detections, the population of GW events provides a unique, and increasingly powerful, avenue to probe a wide range of topics, including fundamental physics [5], cosmology [6,7], and astrophysics [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The direct observation of gravitational waves (GWs) [1] has had a tremendous impact in fundamental physics [2][3][4][5], astrophysics [6][7][8][9][10][11][12][13][14][15], and cosmology [16][17][18], and starting from the observation of the binary neutron star (BNS) signal GW170817 [9] has opened a new era in multi-messenger astronomy with GWs [19][20][21][22]. The third observing run (O3) of Advanced LIGO [23] and Advanced Virgo [24] ended in March 2020, and together these interferometers have found more than 50 GW candidates [25], with 39 candidates observed during the first half of O3 [8].…”
Section: Introductionmentioning
confidence: 99%
“…The posteriors of Planck (Planck Collaboration 2020) and SH0ES (Riess et al 2019) are shown in purple boxes as a guide. Image reproduced with permission from Palmese et al (2020), copyright by AAS position (Soares-Santos et al 2019). For example, if 3 detectors observe the wave with perfect accuracy, the two independent time delays and three measured amplitudes will in turn determine the two sky position angles, two polarisation amplitudes, and one phase lag between polarisations.…”
Section: Gravitational Wavesmentioning
confidence: 99%